(3YbO GddBdi aj GdQO Ydi CHj MGeO GdZRGdis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Gdbjhe GdPi CfWb dSGf GdHQgGf , aCaUM dg HdSGf GdJhMjO hCPYf dg HMbGFb GdYQaGf s
(3BNQgG (B:s
(3hEf jMejce Yf GdEYJbGOGJ GdaGSOI hEJHGY GdCghGA HJhajbg hYUeJg Efg SejY eLjH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B5s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfGhjf HGdMeQIs
(3Ydi MhGTjgG HYV GdJYdjbGJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds